No postnatal maternal effect on male aggressiveness in wild-derived strains of house mice - Dureje, Ludovít; Bímová, Barbora Vošlajerová; Piálek, Jaroslav (Aggressive behavior, 2011)
Male aggressiveness is a complex behavior influenced by a number of genetic and non-genetic factors. Traditionally, the contribution of each of these factors has been established from experiments using artificially selected strains for high/low aggressive phenotypes. However, little is known about the factors underlying aggressive behavior in natural populations. In this study, we assess the influence of genetic background vs. postnatal maternal environment using a set of cross-fostering experiments between two wild-derived inbred strains, displaying high (STRA, derived from Mus musculus domesticus) and low (BUSNA, derived from Mus musculus musculus) levels of aggressiveness. The role of maternal environment was tested in males with the same genetic background (i.e. strain origin) reared under three different conditions: unfostered (weaned by mother), infostered (weaned by an unfamiliar dam from the same strain), and cross-fostered (weaned by a dam from a different strain). All males were tested against non-aggressive opponents from the A/J inbred strain. Resource-holding potential was assessed through body weight gains and territory ownership. The STRA males were shown to be aggressive in both neutral cage and resident-intruder tests. On the contrary, the BUSNA males were less aggressive in all tests. We did not find a significant effect of postnatal maternal environment; however, we detected significant maternal effect on body weight with differences between the strains, fostering type and interactions between these factors. We conclude that the aggressiveness preserved in the two strains has significant genetic component whose genetic basis can be dissected by quantitative trait loci analysis.
Keywords: Behavior, Animal; Aggression; Animals, Wild; Analysis of Variance; mužské pohlaví; Mice; Dominance-Subordination; analýza rozptylu; divoká zvířata; ženské pohlaví; zvířata; Maternal Behavior; agrese; mateřské chování; dominance a subordinace; chování zvířat; Species Specificity; myši; druhová specificita; Female; Male; Animals